Mitochondria, oxidative stress and nonalcoholic fatty liver disease: A complex relationship - Karkucinska-Wieckowska, Agnieszka (2022)
According to the 'multiple-hit' hypothesis, several factors can act simultaneously in nonalcoholic fatty liver disease (NAFLD) progression. Increased nitro-oxidative (nitroso-oxidative) stress may be considered one of the main contributors involved in the development and risk of NAFLD progression to nonalcoholic steatohepatitis (NASH) characterized by inflammation and fibrosis. Moreover, it has been repeatedly postulated that mitochondrial abnormalities are closely related to the development and progression of liver steatosis and NAFLD pathogenesis. However, it is difficult to determine with certainty whether mitochondrial dysfunction or oxidative stress are primary events or a simple consequence of NAFLD development. On the one hand, increasing lipid accumulation in hepatocytes could cause a wide range of effects from mild to severe mitochondrial damage with a negative impact on cell fate. This can start the cascade of events, including an increase of cellular reactive nitrogen species (RNS) and reactive oxygen species (ROS) production that promotes disease progression from simple steatosis to more severe NAFLD stages. On the other hand, progressing mitochondrial bioenergetic catastrophe and oxidative stress manifestation could be considered accompanying events in the vast spectrum of abnormalities observed during the transition from NAFL to NASH and cirrhosis. This review updates our current understanding of NAFLD pathogenesis and clarifies whether mitochondrial dysfunction and ROS/RNS are culprits or bystanders of NAFLD progression.